Thundersnow in Brazil: a case study of 22 July 2013. (6th August 2015) - Dolif Neto, Giovanni; Market, Patrick S.; Pezza, Alexandre Bernardes; Morales Rodriguez, Carlos Augusto; Calvetti, Leonardo; da Silva Dias, Pedro Leite; Escobar, Gustavo Carlos Juan
Abstract: On 23 July 2013, a snowstorm hit southern Brazil causing material damage and two deaths. Radar reflectivity and lightning data revealed a rare thundersnow occurrence. This study revealed that a Rossby wave propagation followed a typical pattern of cold incursions in South America, but some fundamental differences can be pointed out: (1) further northward Rossby wave amplification; (2) strong upward vertical motion within a deep nearly saturated layer and (3) a conditional symmetric instability layer, in response to strong vertical shear, beneath a layer of weak conditional instability, and above a significant near‐surface vertical depth where temperatures hover around 0 °C.